3x(2x+20)=4x-20

Simple and best practice solution for 3x(2x+20)=4x-20 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x(2x+20)=4x-20 equation:


Simplifying
3x(2x + 20) = 4x + -20

Reorder the terms:
3x(20 + 2x) = 4x + -20
(20 * 3x + 2x * 3x) = 4x + -20
(60x + 6x2) = 4x + -20

Reorder the terms:
60x + 6x2 = -20 + 4x

Solving
60x + 6x2 = -20 + 4x

Solving for variable 'x'.

Reorder the terms:
20 + 60x + -4x + 6x2 = -20 + 4x + 20 + -4x

Combine like terms: 60x + -4x = 56x
20 + 56x + 6x2 = -20 + 4x + 20 + -4x

Reorder the terms:
20 + 56x + 6x2 = -20 + 20 + 4x + -4x

Combine like terms: -20 + 20 = 0
20 + 56x + 6x2 = 0 + 4x + -4x
20 + 56x + 6x2 = 4x + -4x

Combine like terms: 4x + -4x = 0
20 + 56x + 6x2 = 0

Factor out the Greatest Common Factor (GCF), '2'.
2(10 + 28x + 3x2) = 0

Ignore the factor 2.

Subproblem 1

Set the factor '(10 + 28x + 3x2)' equal to zero and attempt to solve: Simplifying 10 + 28x + 3x2 = 0 Solving 10 + 28x + 3x2 = 0 Begin completing the square. Divide all terms by 3 the coefficient of the squared term: Divide each side by '3'. 3.333333333 + 9.333333333x + x2 = 0 Move the constant term to the right: Add '-3.333333333' to each side of the equation. 3.333333333 + 9.333333333x + -3.333333333 + x2 = 0 + -3.333333333 Reorder the terms: 3.333333333 + -3.333333333 + 9.333333333x + x2 = 0 + -3.333333333 Combine like terms: 3.333333333 + -3.333333333 = 0.000000000 0.000000000 + 9.333333333x + x2 = 0 + -3.333333333 9.333333333x + x2 = 0 + -3.333333333 Combine like terms: 0 + -3.333333333 = -3.333333333 9.333333333x + x2 = -3.333333333 The x term is 9.333333333x. Take half its coefficient (4.666666667). Square it (21.77777778) and add it to both sides. Add '21.77777778' to each side of the equation. 9.333333333x + 21.77777778 + x2 = -3.333333333 + 21.77777778 Reorder the terms: 21.77777778 + 9.333333333x + x2 = -3.333333333 + 21.77777778 Combine like terms: -3.333333333 + 21.77777778 = 18.444444447 21.77777778 + 9.333333333x + x2 = 18.444444447 Factor a perfect square on the left side: (x + 4.666666667)(x + 4.666666667) = 18.444444447 Calculate the square root of the right side: 4.294699576 Break this problem into two subproblems by setting (x + 4.666666667) equal to 4.294699576 and -4.294699576.

Subproblem 1

x + 4.666666667 = 4.294699576 Simplifying x + 4.666666667 = 4.294699576 Reorder the terms: 4.666666667 + x = 4.294699576 Solving 4.666666667 + x = 4.294699576 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4.666666667' to each side of the equation. 4.666666667 + -4.666666667 + x = 4.294699576 + -4.666666667 Combine like terms: 4.666666667 + -4.666666667 = 0.000000000 0.000000000 + x = 4.294699576 + -4.666666667 x = 4.294699576 + -4.666666667 Combine like terms: 4.294699576 + -4.666666667 = -0.371967091 x = -0.371967091 Simplifying x = -0.371967091

Subproblem 2

x + 4.666666667 = -4.294699576 Simplifying x + 4.666666667 = -4.294699576 Reorder the terms: 4.666666667 + x = -4.294699576 Solving 4.666666667 + x = -4.294699576 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4.666666667' to each side of the equation. 4.666666667 + -4.666666667 + x = -4.294699576 + -4.666666667 Combine like terms: 4.666666667 + -4.666666667 = 0.000000000 0.000000000 + x = -4.294699576 + -4.666666667 x = -4.294699576 + -4.666666667 Combine like terms: -4.294699576 + -4.666666667 = -8.961366243 x = -8.961366243 Simplifying x = -8.961366243

Solution

The solution to the problem is based on the solutions from the subproblems. x = {-0.371967091, -8.961366243}

Solution

x = {-0.371967091, -8.961366243}

See similar equations:

| -9n+19=-8n-14 | | 6(9z-12)=9(5z+11) | | 2x+33?5x+6= | | 100x*10000=250x | | -6+4x+6x=-66 | | 4m-20=20-16m | | y=4x^3-.5x+2 | | 8c-120=240+5c | | 7x+8+4x=-80 | | x^4-20x^3+141x^2-406x+392*x-9=0 | | T(f+9)=40 | | 5y-7y=10 | | 6x-30=60-3x | | 9r-4=44+6r | | 5(2x+-7)-3(3x-10)+4= | | (D^3-D^2-4D-2)y=0 | | 46+16y=572 | | 4x-39=90 | | -17-20=-13x+80 | | 2x+3=9x+12-x | | 4x+2+6x=82 | | -5d+120=-6d-9 | | 8(3G+5R)= | | 14+29m=28+22m | | -8x-22=-3(x-1) | | 4x+17=90 | | 2f+20=101-f | | 2w-18w=-32 | | 32+12y=420 | | 78=3c+12+-1c+4 | | -139=5x+7+5 | | x-38=84 |

Equations solver categories